CHALLENGES TO FREEDOM OF SPEECH AND SAFETY OF JOURNALISM IN UKRAINE - Galyna Piskorska (Інтегровані комунікації)
This study evaluates the dangers and challenges faced by journalists in Ukraine during Russia's full-scale war against the country. The war and the imposition of martial law aimed at ensuring national security have restricted the operational capabilities and freedom of the media. Independent media outlets face severe threats to the lives and work of journalists in occupied areas. Additionally, the Ukrainian authorities sometimes impede journalistic activities by restricting access, controlling information, and persecuting investigative journalists. The author, alongside representatives of the journalistic community and Western partners, asserts that the state's monopolization of the only news channel in Ukraine is unjustified. This research aims to foster broader discussions about the inherent threats that media can pose to national security and the rationale behind restricting freedom of speech during wartime. It is widely believed that high-quality investigative journalism, especially in times of conflict, plays a crucial role in ensuring public oversight of government actions. Such journalism compels the government to act more responsibly, aids in reducing corruption, and facilitates the adoption of essential decisions for the nation's well-being. Despite the restrictions imposed by the war, free and independent media in Ukraine have continued to operate throughout this time, maintaining high standards of their work. A preliminary analysis of scientific sources reveals a lack of comprehensive research on this topic. Individual works of scientists that partially address this issue are examined. Practitioners and specialised international organisations have documented the safety of journalistic activities and freedom of speech. The study employs various research methods, including analysis, observation, description, comparative analysis, analytical and synthetic information processing, generalization, and systematization. The need for continued efforts by Ukrainian media, supported by partners, to uphold the right to freedom of speech and information is emphasized.